Incorporating the e-HIM Virtual Lab into the Health Information Administration Professional Practice Experience - Barefield, Amanda C (Online Learning, 2010)
This article will highlight the experiences of two baccalaureate Health Information Administration (HIA) programs in the adoption of the American Health Information Management Association’s (AHIMA) e-HIM Virtual Laboratory (Virtual Lab) into the Professional Practice Experience (PPE). Information describing the implementation of the Virtual Lab, issues encountered, and subsequent feedback from students and faculty regarding this new technology is provided.